An improved PMUs placement method for power system state estimation - C. Rakpenthai (2018)
This paper presents a technique for improving the phasor measurement units (PMUs) placement method recently proposed by Madtharad. The minimum condition number of the measurement matrix is used as the criteria in conjunction with sequential elimination approach to search optimal placement of this problem. Moreover, in order to minimize the communication cost, a placement-site reduction technique is performed after obtaining the solutions of placement Numerical simulations on small and large sized power systems are compared with the Madtharad's method. The results indicate that the proposed method gives smaller condition number and the number of placement-site is successfully reduced.